2015
DOI: 10.1002/jbm.b.33424
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and finite element analyses of bone cement‐Injectable cannulated pedicle screw fixation in osteoporotic bone

Abstract: The objectives of this study were to investigate the safety and biomechanical stability of a polymethylmethacrylate (PMMA)-augmented bone cement-injectable cannulated pedicle screw (CICPS) in cancellous bone model, and to analyze the stress distribution at the screw-cement-bone interface. The OMEGA cannulated pedicle screw (OPS) and conventional pedicle screw (CPS) were used as control groups. Safety of the CICPS was evaluated by the static bending and bending fatigue tests. Biomechanical stability was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Uniform distribution of the cement effectively avoids clinical complications related to cement leakage into the spinal canal. This type of cannulated screw is putatively significantly better compared with other existing types of cannulated screw systems 13,14.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Uniform distribution of the cement effectively avoids clinical complications related to cement leakage into the spinal canal. This type of cannulated screw is putatively significantly better compared with other existing types of cannulated screw systems 13,14.…”
Section: Discussionmentioning
confidence: 90%
“…We previously demonstrated the improved biomechanical stability of the polymethylmethacrylate (PMMA)-augmented CICPS in osteoporotic bone 13,14. In the present retrospective study, we evaluated the long-term safety and effectiveness of the PMMA-augmented CICPS in 128 osteoporotic patients with degenerative spinal diseases.…”
Section: Introductionmentioning
confidence: 93%
“…A suitable cage was filled with crushed autologous bone for fusion, then rods were installed and nuts were locked. In this study, a new type of PMMA-augmented CPS, named "bone cement injectable cannulated pedicle screw (CICP S)" was developed by the authors for reduction and fixation, a detailed introduction of which was reported in detail in previous studies [17][18][19][20].…”
Section: Surgical Methodsmentioning
confidence: 99%
“…A suitable cage was lled with crushed autologous bone for fusion, then rods were installed and nuts were locked. In this study, a new type of PMMA-augmented CPS named bone cement-injectable cannulated pedicle screw (CICPS) was developed by authors for reduction and xation, a system introduction of which was reported in detail in previous literatures (17)(18)(19)(20).…”
Section: Surgical Methodsmentioning
confidence: 99%